2021
DOI: 10.47120/npl.ms31
|View full text |Cite
|
Sign up to set email alerts
|

NMS 2018-2021 Life-sciences and healthcare project "Digital health: curation of healthcare data" - final report

Abstract: NPL Report MS 31 I TERMINOLOGY Data CurationOrganization and integration of data collected from various sources, annotation of the data, and publication and presentation of the data such that the value of the data is maintained over time, and the data remains available for reuse and preservation. Data Interoperability Addresses the ability of systems and services that create, exchange and consume data to have clear, shared expectations for the contents, context and meaning of that data. Data Integration Aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…NPL runs an ongoing inter-disciplinary Digital Health programme aimed to use data metrology tools to help solve some of the important and emerging challenges of utilising healthcare data [17]. The project includes several case studies, some of which are briefly described below, and further details can be found in the 2021 report [18].…”
Section: Digital Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…NPL runs an ongoing inter-disciplinary Digital Health programme aimed to use data metrology tools to help solve some of the important and emerging challenges of utilising healthcare data [17]. The project includes several case studies, some of which are briefly described below, and further details can be found in the 2021 report [18].…”
Section: Digital Healthmentioning
confidence: 99%
“…We implemented a procedure that includes the device calibration information into the DICOM header information of the patient scan. We expect that the MVCT calibration data can be used to remove the device-related variability and make the patient images more inter-comparable, reduce the variations in the image quality, improving the accuracy of analysis, safety, and efficiency of data-driven clinical interventions [18].…”
Section: Data Processingmentioning
confidence: 99%
“…A further case study in the Digital Health programme evaluates how data linkage can be used to improve the quality of life and long-term treatment outcomes for prostate cancer patients by using the patient care data acquired outside of clinical trials [13]. We developed an ontology-based data curation framework to identify and collate information about diagnosis, symptoms, and treatment side effects from routine primary care electronic health records.…”
Section: Digital Healthmentioning
confidence: 99%